Phrabāt Somdet Phra Paraminthra Mahā Prachāthipok Phra Pokklao Čhaoyūhūa song sala rātchasombat - Prajadhipok, King of Siam, 1893-1941 (Samnakngān Lēkhāthikān, Saphā Phūth̄æn Rātsad̨ōn, 1993)
On life and abdication of Prajadhipok, King of Siam, 1893-1941, leading to beginning of constitutional era in Thailand, 1932; volume commemorating his centenary.